Signal management and risk minimization strategy: a case study on obinutuzumab and non-overt disseminated intravascular coagulation - Valdiserra, Giulia; Mores, Nadia; Rocchi, Rosalba Elisabetta; Sottosanti, Laura; Felicetti, Patrizia; Marchione, Pasquale; Laurenti, Luca; Fresa, Alberto; Bucaneve, Giampaolo; Cappello, Emiliano; Bonaso, Marco; Ferraro, Sara; et al. (Frontiers in Drug Safety and Regulation, 2023)
Introduction: In December 2020, the Italian Medicines Agency (AIFA) in collaboration with the Italian Regional Centers of Pharmacovigilance evaluated four individual case safety reports (ICSRs) reporting obinutuzumab and non-overt disseminated intravascular coagulation (DIC) as a new possible signal. In this study, we described the process of signal management for obinutuzumab-associated non-overt DIC. Methods: In accordance with the Guideline on Good Pharmacovigilance Practices Module IX, we described the process of the Italian and European Union signal management process in five steps: signal detection, signal validation, signal confirmation, signal analysis, and prioritization and signal assessment. Results: In the signal detection phase, four cases of obinutuzumab-associated non-overt DIC met the criteria for signal definition (ROR 213.6 and IC025 77). In the signal validation phase, both the Italian and European databases of spontaneously reported adverse drug reactions were investigated with supporting evidence from medical literature. Four patients (two men and two women aged 67–77) were in treatment with obinutuzumab for chronic lymphocytic leukemia, and they developed a subclinical DIC within 24 h from the administration of the drug. The DIC spontaneously resolved in all cases. Three more ICSRs were reported in the EudraVigilance database. The medical literature provided poor evidence of the possible association between obinutuzumab and DIC. The signal was subsequently validated, first by AIFA and then by EMA. The signal was confirmed by the Pharmacovigilance Risk Assessment Committee (PRAC) Rapporteur in the “signal confirmation” phase, and it entered “signal analysis and prioritization” and “signal assessment”. In these phases, the PRAC assessed and confirmed DIC as a possible adverse reaction to obinutuzumab. Finally, the Summary of Product characteristics was updated with this new risk. Conclusion: Despite the intrinsic difficulties linked to the nature of the event itself, the process of signal detection and the issuing of the risk minimization measures by the Italian Medicines Agency as part of the EU procedures have proven to be efficient.